The relationship between lunch break autonomy and employee creativity: Positive affect as a mediator - Limbang, Eddie Jr (2023)
Self-Determination Theory (SDT) and studies suggest that fulfilling psychological needs such as autonomy leads to the generation of energy and hence, decreases fatigue. Literature has suggested that the presence of lunch break autonomy (LBA), the autonomy that employees feel during a lunch break, reduces the fatigue resulting from activities such as working during a break or socializing with others from the office. Studies have also found a positive association between autonomy and creativity. Therefore, LBA is assumed to have a positive relationship with creativity at work. However, there are limited studies on the relationship between LBA and employees’ creativity and the underlying mechanism of the relationship is unexplored. Studies have indicated that the fulfillment of autonomy is associated with positive affect, which is conducive to creativity. The present study investigated the relationship between LBA and creativity and the hypothetical mediating role of positive affect in the aforementioned relationship among working Malaysians. utilizing a cross-sectional design. Based on the suggestion of the online monte carlo power analysis for indirect effects calculator, 191 responses from employees in creative industries were collected and analyzed. These participants answered the lunch break autonomy subscale of the Recovery Experience Questionnaire, Positive and Negative Affect Schedule, and self-rated creativity scale to measure LBA, positive affect, and creativity respectively. For the control variable, the psychological detachment subscale from the Recovery viii Experience Questionnaire was utilized. The findings are aligned with the study’s hypothesis that LBA is indirectly associated with creativity through positive affect. These findings offer insights into the importance of effective lunch break policies that encourage autonomy and a potential way to cultivate employees creativity for organizations to consider.